Factors associated with the CVD risk factors and body fat pattern of postmenopausal Hindu caste and Lodha tribal populations living in India: An exploratory study - Debasmita Kar; Subho Roy (Women's Midlife Health, 2023)
Abstract Background Loss in ovarian function during mid-life results in adverse changes in the cardiovascular profile of women. The association between CVD risk factors and menopause differ cross-culturally since several modifiable factors play significant roles in explaining CVD mortality in addition to differences in endogenous estrogen. Very few of the studies from the Indian subcontinent have been concerned with the menopause-specific CVD risk factors, particularly among the tribal groups. Thus, we intended to study the variations in body fat pattern and CVD risk factors between Hindu caste and Lodha tribal postmenopausal women and how these risk factors were associated with differential socio-economic, reproductive and menstrual characteristics and lifestyle variables. The Lodha tribal populations is considered a Particularly Vulnerable Group (PVTG) in this country. Methods This cross-sectional study was conducted among the Bengali Hindu caste and Lodha tribal populations of the State of West Bengal, India covering three districts namely Howrah, Jhargram and East Midnapure. A total of 197 postmenopausal participants were recruited for this study (urban caste 69, rural caste 65 and rural Lodha 63). Data on blood glucose and total cholesterol levels, blood pressure, muscle mass, body fat distribution and sociodemographic, reproductive and menstrual history and lifestyle variables were collected following standard protocols. Analysis of variance (ANOVA) was applied to compare blood glucose, total cholesterol and blood pressure levels and body fat measures across the three populations. Stepwise multiple linear regression analysis was performed to find out the factors associated with CVD risk factors. The data were analyzed with the Statistical Package for Social Science version 20.0(IBM corporation, 2011). Results This cross-sectional comparison of women at midlife, though exploratory in nature showed significant differences in body fat pattern and CVD risk factors between caste and tribal groups owing to socioeconomic disparities and, differences in reproductive characteristics and lifestyle factors. Conclusion The caste and tribal populations differed significantly in body fat pattern and CVD risk factors and in the factors associated with CVD risk suggesting interplay between menopause and modifiable factors in explaining CVD risk factors during mid-life.